THE TRANSLATION OF IDIOMS FROM DUBBING OF THE SERIES EL CHAVO DEL 8 FOR TEACHING SPANISH AS A FOREIGN LANGUAGE - Fernandez Quiroz, Ariel Marcelo [UNESP]; Pinto, Paula Tavares [UNESP] (Unesp-faculdade Ciencias & Letras, 2018)
Idioms are formulaic constructions specific to each language and culture that, in the field of teaching a foreign language, deserve special attention. The unconscious translation process performed by students in the classroom should conflict when literally translating such expressions, because not all of them have a grammatically and syntactically similar equivalent in the target language. In this article, we try to offer a theoretical basis that will help teachers understand how to position themselves in front of students when teaching idioms in Spanish and how to approach this content. To achieve this, we are based on the definition of idioms given by Dicionario Priberam da Lingua Portuguesa, on the theoretical basis of idiomatic expression (XATARA, 1998), equivalence (HURTADO ALBIR, 2001), levels of learning of idiomatic expressions (RIOS, 2010), and translation in the acquisition of foreign languages (HARBORD, 1992). To help with this process, we present fifteen examples of Spanish idioms extracted from nine episodes of the Mexican series El Chavo del 8, with their respective meanings and equivalences in Portuguese.
Keywords: Idiom; Equivalence; Translation; Teaching spanish as a foreign language